Exploring serendipitous relief: SSRIs as a potential treatment for aphthosis - a case report - Gambolò, Luca; D'Angelo, Marta; Stirparo, Giuseppe (Aesthetic Medicine, 2023)
Recurrent aphthous stomatitis (RAS) is a common and challenging inflammatory condition of the oral mucosa. The aetiology of RAS is multifactorial, and effective management options are currently limited. This case report explores an unexpected finding in the treatment of RAS, focusing on a patient treated with selective serotonin reuptake inhibitors (SSRIs) for anxiety and social phobia who experienced the resolution of aphthous stomatitis symptoms. A young male patient (LR) with infrequent periods of obsessions and compulsions, along with social phobia and panic attacks, was prescribed a daily dose of 20 mg of paroxetine. Remarkably, LR ceased experiencing episodes of aphthosis approximately two months after starting treatment. The improvement in RAS symptoms has been sustained for a duration of four years. This case report presents a unique finding in the management of RAS, with SSRIs, particularly paroxetine, demonstrating an unexpected collateral effect on the resolution of aphthous stomatitis symptoms. Previous reports have primarily involved monoamine oxidase inhibitors (MAOIs), and literature lacks clinical trials specifically evaluating the efficacy of SSRIs in treating aphthous stomatitis. Further research is warranted to elucidate the underlying mechanisms and establish the efficacy of SSRIs in larger-scale clinical studies. The collateral improvement of RAS symptoms in a patient being treated with an SSRI suggests a potential alternative treatment approach for this challenging condition. However, given the limitations of this single case report, further research is necessary to replicate these findings and evaluate the safety and efficacy of SSRIs in managing RAS.